The Institutional Architecture and the Fulfilment of the 2030 Agenda in Iberoamerica - Arenilla Sáez, Manuel (Revista del CLAD Reforma y Democracia, 2019)
The 2030 Agenda for Sustainable Development requires an institutional architecture that facilitates its governance and enables Iberoamerican countries to strengthen the necessary capacities to effectively meet the Sustainable Development Goals (SDG). A good institutional design is required to achieve political and social confidence, certainty and democratic stability. The conception of the State and the Administration as a platform in which numerous actors interact to achieve the common good by means of the public drive is an essential element for the success of the Agenda 2030 and their SDG. This research contemplates the combination of factors or means and administrative functions as the basis of institutional strength. From here and the analysis of academic studies, documentation of numerous agencies, and Iberoamerican countries Voluntary National Reviews, the following variables arise to be considered in the design of an adequate institutional architecture: effective leadership, institutional mechanisms, institutional capacity, intergovernmental relations and participation / communication, which have been broken down into several dimensions. The research makes a series of proposals to improve the institutional architecture for the fulfilment of the 2030 Agenda in Iberoamerica.It is decisive in leadership to attribute the impulse of the 2030 Agenda to an organism with effective powers of coordination orplanning on territorial and governmental agencies involved. It is necessary to make an effort in organizational simplification, in the integration of SDG into national planning mechanisms and the effective participation of the social actors. The budgetary and financial factor and statistics are having impact on the SDG in Iberoamerica. The territorialisation of the SDG is scarce, as also the regional and global alliances. The improvement of intergovernmental aspects and cooperation should be completed with a review of the international financing mechanisms. It is necessary to establish actual participation between social organizations and enterprises and public institutions.